2019
DOI: 10.5812/semj.81115
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Health Literacy in the Iranian Population: Findings and Implications

Abstract: Context: Health literacy includes social and cognitive skills determining individuals' motivation to obtain and understand health information, thus empowers them to promote healthy behaviors. The exact level of health literacy in the Iranian population is unknown, as different Iranian studies have reported different health literacy rates in the Iranian population. Objectives: Therefore, this study aimed to investigate health literacy in the Iranian population by systematically combining and analyzing findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
0
15
1
Order By: Relevance
“…In the initial paper derived from the project reporting the urban-rural differences in HL and its determinants [21], we concluded that the differences found in FHL by geographic location may originate from the disparities in the number of family members, educational status, monthly income, and history of contact with the healthcare system between urban and rural areas. Previous research has also demonstrated geographic location as an effective factor on FHL [18]. Playing the role of a source for many in uential factors on FHL, geographic location seems to be a basic social determinant with great in uence on HL.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In the initial paper derived from the project reporting the urban-rural differences in HL and its determinants [21], we concluded that the differences found in FHL by geographic location may originate from the disparities in the number of family members, educational status, monthly income, and history of contact with the healthcare system between urban and rural areas. Previous research has also demonstrated geographic location as an effective factor on FHL [18]. Playing the role of a source for many in uential factors on FHL, geographic location seems to be a basic social determinant with great in uence on HL.…”
Section: Discussionmentioning
confidence: 91%
“…Despite such remarkable disparities in HL and its determinants, healthcare services to urban-rural populations in many MENA region countries, like Iran, are still delivered with a lack of attention in equity considerations [40]. Although some contemporary efforts are made by the Iranian government to promote general literacy within the society, there are still remarkable gender-based disparities in health and wellbeing between the urban and rural inhabitants [18]. In order to decrease such disparities, promoting the level of internet use through increasing the level of internet accessibility and internet use skills as well as HL education through social and mass media campaigns are recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial paper derived from the project reporting the urban-rural differences in health literacy and its determinants (25), we concluded that the differences found in FHL by geographic location may originate from the disparities in the number of family members, educational status, monthly income, and history of contact with the health care system between urban and rural areas. Previous research has also demonstrated geographic location as an effective factor on FHL (22). Playing the role of a source for many in uential factors on FHL, geographic location seems to be a basic social determinant with great in uence on health literacy.…”
Section: Discussionmentioning
confidence: 94%
“…Although in the Middle East and North African (MENA) region countries a number of studies have been carried out to investigate health literacy measures (20)(21)(22)(23)(24), among older adults and patients with chronic diseases (22), as well as the determination of HL (25), few studies have previously investigated the contribution of different socio-demographic factors to HL, and the associations between gender and health literacy in the region. Also, a majority of previous studies has only investigated the associations between socio-demographic characteristics and HL.…”
Section: Introductionmentioning
confidence: 99%